Ampicillin therapy of experimental enterococcal endocarditis. - Tight, R R (1980)
In rabbits with experimental enterococcal endocarditis, subcutaneously implanted perforated polyethylene chambers were used for ampicillin administration by intra-chamber injection. A total of 21 days of intra-chamber ampicillin therapy sterilized vegetations of 14 out of 14 rabbits with experimental enterococcal endocarditis. In rabbits treated for less than 21 days, the duration of therapy and quantitative vegetation cultures were inversely related. Peak serum minimal bactericidal titers were greater than or equal to 1:8 in 94% of the determinations. Trough serum minimal bactericidal titers were less than or equal to 1:2. The mean trough serum ampicillin concentration (2.6 micrograms/ml) was greater than the minimal bactericidal concentration of ampicillin for the infecting enterococcus and less than the mean trough chamber fluid ampicillin concentration (3.7 micrograms/ml). Relatively prolonged therapy with intrachamber injections seemed to be well tolerated. Combination drug therapy of enterococcal endocarditis may not always be required. The maintenance of serum minimal bactericidal titers greater than or equal to 1:8 throughout the therapy of endocarditis, as is often recommended, may be unnecessary.